Validating a New GNSS-Based Sea Level Instrument (CalNaGeo) at Senetosa Cape. Issue 2 (4th March 2022) - Bonnefond, Pascal; Laurain, Olivier.; Exertier, Pierre; Calzas, Michel; Guinle, Thierry; Picot, Nicolas
Abstract: The geodetic Corsica site was set up in 1998 in order to perform altimeter calibration of the TOPEX/Poseidon (T/P) mission and subsequently, Jason-1, OSTM/Jason-2, Jason-3 and more recently Sentinel-6 Michael Freilich (launched on November, 21 2020). The aim of the present study held in June 2015 is to validate a recently developed GNSS-based sea level instrument (called CalNaGeo) that is designed with the intention to map Sea Surface Heights (SSH) over large areas. This has been undertaken using the well-defined geodetic infrastructure deployed at Senetosa Cape, and involved the estimation of the stability of the waterline (and thus the instantaneous separation of a GNSS antenna from water level) as a function of the velocity at which the instrument is towed. The results show a largely linear relationship which is approximately 1 mm/(m/s) up to a maximum practical towing speed of ∼10 knots (∼5 m/s). By comparing to the existing "geoid" map, it is also demonstrated that CalNaGeo can measure a sea surface slope with a precision better than 1 mm/km (∼2.5% of the physical slope). Different processing techniques are used and compared including GNSS Precise Point Positioning (PPP, where the goal is to extend SSH mapping far from coastal GNSS reference stations) showing an agreement at the 1-2 cm level.